What determines financial inclusion in Sub-Saharan Africa?. Issue 1 (13th March 2017) - Chikalipah, Sydney
Abstract : Purpose: The purpose of this paper is to investigate the determinants of financial inclusion (FI) in Sub-Saharan Africa (SSA). Design/methodology/approach: The paper uses the World Bank country-level data from 20 SSA countries for the year 2014. Findings: The empirical findings in this study indicate that illiteracy is the major hindrance to FI in SSA. The findings provide useful information to government agencies and international development organisations. Also, the findings can help accelerate and strengthen FI strategies among SSA countries. Research limitations/implications: Some countries were excluded from the final analysis due to lack of data. Practical implications: In the last two decades, there has been renewed interest in fighting financial exclusion in Africa. Therefore, this study provide evidence which clearly shows that enhancing literacy levels in a country can immensely contribute towards building the financially inclusive societies in the SSA region. Originality/value: To the best of the author's knowledge, this is the first study to empirically test the determinants of FI in SSA using the World Bank FI data set. Furthermore, this is the first attempt to estimate the determinants of FI with a combined data of SSA countries.